Differences in responses to Wheat dwarf virus infection in contrasting wheat cultivars Ludwig and Svitava - Jan Ripl; Tomáš Dráb; Sebastien Gadiou; Jiban Kumar Kundu (Plant Protection Science, 2020)
The two contrasting cultivars, the very susceptible Ludwig and moderately susceptible Svitava, previously evaluated in field trials to determine their resistance levels to Wheat dwarf virus (WDV), were analysed by four different test methods to allow for the comparison of the methods and to consider whether the resistance level of cv. Svitava can be an effective component of wheat protection from the virus. The differences in the proportion of the diseased plants were observed after the inoculation by the viruliferous leafhoppers. The differences in the cultivar resistance levels were evaluated by comparing the biomass production after the infection. The amount of viral DNA was determined using quantitative polymerase chain reaction (PCR). Concurrently, the cultivar response to the virus infection after the controlled inoculation by the leafhoppers [Psammotettix alienus (Dahlbom, 1850)] under field conditions was further evaluated. The infected plants of cv. Svitava produced five times more dry matter in the vegetative growth stage than cv. Ludwig. The quantitative PCR analysis confirmed the resistance in cv. Svitava. The plant inoculation under a standardised infection pressure showed that the probability of the WDV infection after the inoculation feeding is smaller in the cv. Svitava plants. The comparison of the results from the different test methods shows that the field resistance tests are necessary to obtain a proper assessment of the possibilities for the cultivars' utilisation in the crop protection.